De novo transcriptome assembly with ABySS - Birol, I.; Jackman, S.; Nielsen, C.; Qian, J.; Varhol, Richard; Stazyk, G.; Morin, R.; Zhao, Y.; Hirst, M.; Schein, J.; Horsman, D.; Connors, J.; et al. (Oxford University Press, 2009)
Motivation: Whole transcriptome shotgun sequencing data from non-normalized samples offer unique opportunities to study the metabolic states of organisms. One can deduce gene expression levels using sequence coverage as a surrogate, identify coding changes or discover novel isoforms or transcripts. Especially for discovery of novel events, de novo assembly of transcriptomes is desirable. Results: Transcriptome from tumor tissue of a patient with follicular lymphoma was sequenced with 36 base pair (bp) single- and paired-end reads on the Illumina Genome Analyzer II platform. We assembled ~194 million reads using ABySS into 66 921 contigs 100 bp or longer, with a maximum contig length of 10 951 bp, representing over 30 million base pairs of unique transcriptome sequence, or roughly 1% of the genome. © The Author 2009. Published by Oxford University Press. All rights reserved.